2017
DOI: 10.1167/17.14.6
|View full text |Cite
|
Sign up to set email alerts
|

Serial dependencies act directly on perception

Abstract: There is good evidence that biological perceptual systems exploit the temporal continuity in the world: When asked to reproduce or rate sequentially presented stimuli (varying in almost any dimension), subjects typically err toward the previous stimulus, exhibiting so-called "serial dependence." At this stage it is unclear whether the serial dependence results from averaging within the perceptual system, or at later stages. Here we demonstrate that strong serial dependencies occur within both perceptual and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

39
285
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 198 publications
(349 citation statements)
references
References 31 publications
39
285
4
Order By: Relevance
“…Serial dependence was shown to act directly on perception (Cicchini et al, 2017;, biasing the appearance of our current percept and, hence, it has a perceptual component. Perceptual decisions were also proposed as a necessary component of serial dependence (Fritsche et al, 2017; but see Cicchini et al, 2017), but our results cannot be entirely explained by this. On each trial, observers make a decision regarding the emotional expression they are presented with.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Serial dependence was shown to act directly on perception (Cicchini et al, 2017;, biasing the appearance of our current percept and, hence, it has a perceptual component. Perceptual decisions were also proposed as a necessary component of serial dependence (Fritsche et al, 2017; but see Cicchini et al, 2017), but our results cannot be entirely explained by this. On each trial, observers make a decision regarding the emotional expression they are presented with.…”
Section: Discussionmentioning
confidence: 98%
“…Participants then saw a test screen containing a random adjustment face, which they modified by scrolling through the continuous expression wheel to match the target expression. After picking a match expression, participants saw a 1000-ms noise mask followed by a 1000-ms fixation cross before the next trial began Cicchini et al, 2014;Cicchini, Mikellidou, & Burr, 2017;Corbett et al, 2011;Liberman et al, 2014;Manassi et al, 2017). In Experiment 3, serial dependence was not ethnicity selective.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using continuous measures of perception (reproducing the presented stimuli or rating 4 on a scale), it has been shown that visual perception at a given moment is biased towards the 5 recently seen stimuli (i.e., a positive serial dependence). This has been established for various 6 attributes, from basic features including orientation (Cicchini, Mikellidou, & Burr, 2017;7 Fischer & Whitney, 2014; Fritsche, Mostert, & de Lange, 2017) and numerosity (Cicchini,8 Anobile, & Burr, 2014) to face identity (Liberman, Fischer, & Whitney, 2014). Using 9 categorization tasks, positive serial dependence was found for attributes such as orientation 10 (Cicchini et al 2017;Norton, Fleming, & Daw, 2017), motion (Alais, Leung, & Van der Burg, 11 2017) and gender of face (Taubert, Alais, & Burr, 2016), while a repulsive serial dependence 12 was found for motion-induced orientation (Alais et al, 2017), facial expression (Taubert et al, 13 2016).…”
mentioning
confidence: 99%